Characterize the Speed of a Photon-Number-Resolving Superconducting Nanowire Detector - Xu Tao; Hao Hao; Xiang Li; Shi Chen; Libo Wang; Xuecou Tu; Xiaoqing Jia; Labao Zhang; Qingyuan Zhao; Lin Kang; Peiheng Wu (IEEE Photonics Journal)
Superconducting series nanowire single-photon detectors (SNDs) have been used for resolving photon numbers. But it can also exhibit a higher counting rate than a single superconducting nanowire single-photon detector (SNSPD), because the serial architecture allows multiple detectors working in parallel and the inductance of each pixel is reduced. In this paper, we found each pixel of the SND could reset fast although the whole detector took a much longer time for recovering. Therefore, the speed of an SND with a large kinetic inductance of 1.25 μH was characterized and compared to a standard SNSPD with the same total inductance. By measuring the detected photon rate over the input photon rate, we obtained a photon counting rate enhancement by 7.5 times. Meanwhile, the timing jitter of the SND was 63 ps at single photon detection regime. Our results show that the series structure and the readout scheme are quite practical in realizing high speed single-photon detectors besides resolving photon numbers.